1980
DOI: 10.1038/sc.1980.48
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic evaluation: periurethral striated EMG versus perianal striated EMG

Abstract: Abstract. Fifty consecutive spinal injury patients who underwent simultaneous EMG of the peri-urethral and perianal striated muscles along with cystometrogram on a multiple channel recorder are analysed. Bladder filling, voiding and also influence of spasticity on the EMG activity of both perianal and periurethral striated muscles were compared. Periurethral striated EMG along with CMG has a better diagnostic value (95 per cent) as compared to perianal EMG-CMG which was diagnostic in 72 per cent patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 9 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…Anal sphincter activity registration, as an indirect measurement of urethral sphincteric function, has been used widely but it has been shown that in some cases there exists a difference (Perkash, 1980, Koyanagi et at., 1982. In this work anal sphincter activity was helpful in planning the mode of surgical treat ment for outlet obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Anal sphincter activity registration, as an indirect measurement of urethral sphincteric function, has been used widely but it has been shown that in some cases there exists a difference (Perkash, 1980, Koyanagi et at., 1982. In this work anal sphincter activity was helpful in planning the mode of surgical treat ment for outlet obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a study in incomplete spinal cord injury, using surface anal sphincter EMG signals and the pudendo‐anal reflex, has demonstrated increasing activity with bladder filling . However, it is uncertain as to whether there would always be uniform synergy of responses in the anal and urethral sphincters as it has been shown that in only about 70% of patients with SCI was the anal sphincter EMG diagnostic of urodynamic abnormality as against 90% for the urethral sphincter . Ideally, confirmation through direct recordings from the urethral sphincter of the results obtained here may be required before confidently extrapolating the findings to the influence of corticospinal drive on the urethral sphincter.…”
Section: Discussionmentioning
confidence: 81%
“…These problems become less significant with increasing severity of neuro pathology, so that while with incomplete lesions a random-EMG of the pelvic floor is sufficient to document the activity of the external sphincter, in incomplete lesions of any aetiology a separate evaluation of the peri urethral striated EMG and anal sphincter EMG is advisable (Vereecken and Verduyn, 1970;Perkash, 1980). Uroflowometry and pressure profiles (Sunder et al, 1978;Clarke and Thomas, 1981), as single investigations are useful to understand the underlying pathophysiology but are of limited diagnostic clinical value for paraplegics.…”
Section: Discussionmentioning
confidence: 99%